Education on the use of butterfly pea flowers (Clitoria ternatea) as an antibacterial agent in handwashing soap for students at SDN Pedurungan Kidul 04 Semarang - Dwi Endah Kusumawati; Wilda Fhitriany Usman; Asih Puji Lestari; Nita Tiara Luthfiah; Mifta Triwahyuni (Community Empowerment, 2023)
Washing hands with soap is an effort to prevent transmission of diseases caused by germs. Generally, the antibacterial substance in liquid soap is triclosan, but the use of triclosan is known to kill the good flora on the skin. Butterfly pea flower (clitoria ternatea) contains secondary metabolites which are known to have antibacterial activity such as flavonoids, saponins, alkaloids and tannins so it can be used as a substitute for triclosan. The program aims to increase the knowledge about the use of natural ingredients to be processed into liquid soap. The activity began with a pre-test, continued with a education and workshop on making liquid soap from a mixture of butterfly pea extract and surfactants, and ended with a discussion and post-test. The result of this activity showed that students were able to create butterfly pea flower handwashing soap, as indicated by a 100% increase in their knowledge and skills.